Tap Test Can Predict Cognitive Improvement in Patients With iNPH—Results From the Multicenter Prospective Studies SINPHONI-1 and –2 - Nakajima, Madoka; Yamada, Shigeki; Miyajima, Masakazu; Kawamura, Kaito; Akiba, Chihiro; Kazui, Hiroaki; Mori, Etsuro; Ishikawa, Masatsune, The SINPHONI-2 Investigators; Hashimoto, Masaaki; Origasa, Hideki; Yamamoto, Haruko; et al. (Frontiers in Neurology, 2021)
Background: We analyzed the predictive value of the tap test (TT) on outcome of cerebrospinal fluid (CSF) shunting in patients with idiopathic normal pressure hydrocephalus (iNPH) and cognitive impairment up to 12-months postoperatively. Methods: We analyzed the data of two prospective multicenter studies on ventriculoperitoneal shunt (VPS) and lumboperitoneal shunt (LPS) use in iNPH patients. We selected patients with mini-mental state examination (MMSE)-scores ≤26 points as study subjects. We used a multivariate logistic regression model to obtain the optimal threshold of MMSE-scores after TT to predict the score improvement at 12-months following shunting and that helped to control for confounding factors such as age and MMSE-scores before TT. We used logistic regression models to identify variables with age-adjusted odds ratio (A-OR) and multivariate-adjusted OR (M-OR). Results: For an improvement ≥3-points in the MMSE-score cut-off 7-days following TT in VPS and LPS cohort studies, the MMSE-scores improved by 6-points after 12-months. The VPS cohort had a sensitivity, specificity, and area under the curve (AUC) of 69.2%, 73.7%, and 0.771, respectively, however for the LPS cohort they were 86.2%, 90.9%, and 0.906, respectively. For MMSE-scores that improved by ≥3 points in patients after the TT, the possibility of an improvement by 6-points at 12-months following CSF shunt had A- OR 7.77 and M-OR 6.3 times for the VPS, and A-OR 62.3 and M-OR 59.6 times for the LPS cohort. Conclusion: CSF shunting contributes to improved cognitive function in iNPH patients. Furthermore, MMSE-score evaluation at the TT can sensitively predict improvement in postoperative MMSE-scores following LPS intervention.